Behavior of RC beams strengthened with CFRP sheets under sustained loads. (October 2021) - Al-Khafaji, Ayssar; Salim, Hani; El-Sisi, Alaa
Abstract: This paper investigates the long-term response of reinforced concrete (RC) beams strengthened with CFRP subjected to sustained static loads. The beams were strengthened using two different configurations of CFRP with different steel reinforcement ratios and web reinforcement. Two RC beams and five CFRP-RC beams were evaluated under static short-term bending, and five additional CFRP-RC beams were evaluated under sustained loads for 332 days. The sustained loads were maintained at around 60% of the static capacity of the beams strengthened with CFRP. The residual strength of the CFRP-RC beams after long-term creep testing was evaluated experimentally under static loads to failure. CFRP sheets were attached to the transverse and tension faces of the beams. The test results show that CFRP strengthening of beams is effective in enhancing their static capacities. The residual strength of the long-term creep-tested beams was 5–18% lower than the strength of the short-term beams except for the steel over-reinforced beam. In addition, the residual stiffness did not change significantly. However, the residual toughness was 22% to 64% of the toughness of the short-term beams due to creep damage. The web steel reinforcement played an important role in improving the overall performance and failure mode of the strengthened beams.